2017
DOI: 10.1002/pits.22097
|View full text |Cite
|
Sign up to set email alerts
|

An updated analysis of author affiliation across four school psychology journals: Is practitioner research increasing?

Abstract: This study analyzed articles published in four school psychology journals (Journal of School Psychology, Psychology in the Schools, School Psychology Quarterly, and School Psychology Review) between the years 2009 and 2015. Articles were classified based on whether they were narrative or empirical, and affiliation of each author was classified as either practitioner or university. Results were compared to those of a previous study that similarly classified articles from 2000 to 2008. Across the years, the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Eleven categories for research articles, plus a category of "other" (descriptive, not practice oriented), were recorded. Consistent with Carroll et al (2009) and Aspiranti et al (2018), most authors in the 671 articles reviewed by Little et al (2011) were university affiliated. The most frequent article type observed was "other" (33.1%), which notably was the default category for coding content that did not fit within the research-oriented categories.…”
Section: Development Of Professional Literature In School Psychologymentioning
confidence: 73%
See 2 more Smart Citations
“…Eleven categories for research articles, plus a category of "other" (descriptive, not practice oriented), were recorded. Consistent with Carroll et al (2009) and Aspiranti et al (2018), most authors in the 671 articles reviewed by Little et al (2011) were university affiliated. The most frequent article type observed was "other" (33.1%), which notably was the default category for coding content that did not fit within the research-oriented categories.…”
Section: Development Of Professional Literature In School Psychologymentioning
confidence: 73%
“…A study by Caroll and colleagues (2009) of four major school psychology journals published between 2000 and 2008 was extended by Aspiranti et al (2018); they conducted a content analysis of the same four school psychology journals as Carroll et al but covered the years 2009 through 2015. The findings of Aspiranti et al (2018) were consistent with those of the Caroll and colleagues (2009) study: Aspiranti et al identified limited contributions to the evidence base by clinical practitioners compared to university affiliated authors; the proportion of university affiliated authors increased over time compared to clinical practitioner authors; further, clinical practitioners were suggested as more likely to collaborate in their research endeavors and thus participate as secondary authors. This gap between the research produced in a controlled academic environment and clinical practitioners working in the field was viewed as a barrier to implementation of interventions.…”
Section: Development Of Professional Literature In School Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is essential to examine the quantity and quality of published research, it is also important to understand what type of research is being published. Some researchers have examined the types of published research in terms of general categories of narrative and empirical articles (Aspiranti, McCleary, & Ratliff, 2018;Bliss, Skinner, Hautau, & Carroll, 2008;Carroll, Skinner, McCleary, Hautau von Mizener, & Bliss, 2009;Floyd et al, 2011;Villarreal, Gonzalez, McCormick, Simek, & Yoon, 2013). The category of empirical articles can be broken into types of quantitative and qualitative research, such as descriptive, correlational and causal-comparative.…”
Section: Article Contentmentioning
confidence: 99%
“…The category of empirical articles can be broken into types of quantitative and qualitative research, such as descriptive, correlational and causal‐comparative. In school psychology journals between 2009 and 2015, 77% of the articles published were empirical research studies (Aspiranti et al, ).…”
Section: Article Contentmentioning
confidence: 99%